Patrons and designers - projects for Orthodox churches in Višegrad, Zenica, Blažuj, Trnovac and Vodjenica - Ljiljana Ševo (AGG+, 2019)
There are more than forty projects for building Orthodox churches preserved in the Archives of Bosnia and Herzegovina in Sarajevo. Presented here are four projects for the churches with domes and one for three-conchal building with no dome.The oldest projects are those of Višegrad (dated from 1882) and Zenica (dated from 1889), which represents the church built between 1883-1885. Name of the architect remains unknown in both cases– a project for the church in Višegrad is not signed and signatures of Franz Blazek and perhaps Miloš Komadina on a project for the church in Zenica are not a proof of them being the authors. Projects testify the wishes of the church patrons for their temples to show connection with the Serbian sacral architecture of the 13th century (Višegrad) or to visually manifest growing economic power and social standing of the Serbian Orthodox community, building their church similar to the cathedral in Sarajevo (Zenica). Project for the St Sava church in Blažuj was created in 1895/96, following wishes of the patrons, representatives of the Church community. Project of August Butschа embodied the idea of national recognition in historicist neo-byzantine style created by famous architect of historicism Teophil Hansen, which was back in the time generally recognized as a neo-Byzantine style, and in this specific case as an Orthodox and Serbian one. “Serbian-Byzantine style” of the mausoleum chapel of Lower Tuzla merchants Jovanovićs at Trnovac was almost for sure initiated by their wishes, and the chapel was built in 1889 by well-thought design of the architect Franz Blazek. Neo-Moravska three-conchal basis of Vodjenica church, projected in 1911 by Milos Miladinovic, can be considered as an aspiration of the church patrons to have their temple look like Mostanica.Projects presented can be considered as rare testimonies to the role that “carriers of the patronage mechanism in the process of originating and forming of the church architecture” had in Bosnia and Herzegovina in the Austro-Hungarian period, when the lack of national state resulted in lack of a clear view of the sacral construction forms that would express its identity.